Reproductive risks and preimplantation genetic testing intervention for X–autosome translocation carriers. Issue 1 (July 2021) - Yuan, Shimin; Cheng, Dehua; Luo, Keli; Li, Xiurong; Hu, Liang; Hu, Hao; Wu, Xianhong; Xie, Pingyuan; Lu, Changfu; Lu, Guangxiu; Lin, Ge; Gong, Fei; et al.
Abstract: Research question: What is the genetic cause of multiple congenital disabilities in a girl with a maternal balanced X–autosome translocation [t(X-A)]? Is preimplantation genetic testing (PGT), to distinguish non-carrier from euploid/balanced embryos and prioritize transfer, an effective and applicable strategy for couples with t(X-A)? Design: Karyotype analysis, whole-exome sequencing and X inactivation analysis were performed for a girl with congenital cardiac anomalies, language impairment and mild neurodevelopmental delay. PGT based on next-generation sequencing after microdissecting junction region (MicroSeq) to distinguish non-carrier and carrier embryos was used in three couples with a female t(X-A) carrier (cases 1–3). Results: The girl carried a maternal balanced translocation 46, X, t(X;1)(q28;p31.1). Whole-exome sequencing revealed no monogenic mutation related to her phenotype, but she carried a rare skewed inactivation of the translocated X chromosome that spread to the adjacent interstitial 1p segment, contrary to her mother. All translocation breakpoints in cases 1–3 were successfully identified and each couple underwent one PGT cycle. Thirty oocytes were retrieved, and 13 blastocysts were eligible for biopsy, of which six embryos had a balanced translocation and only four were non-carriers. Three cryopreserved embryo transfers with non-carrier status embryos resulted in the birth of two healthy children (one girl and one boy), who were subsequently confirmed to have normal karyotypes. Conclusions: This study reported a girl with multiple congenital disabilities associated with a maternal balanced t(X-A) and verified that the distinction between non-carrier and carrier embryos is an effective and applicable strategy to avoid transferring genetic and reproductive risks to the offspring of t(X-A) carriers.